A study to determine the knowledge attitudes and practices of emergency contraception among women seeking abortion at Kitwe Central Hospital - Bwanali, Lillian (Lusaka: University of Zambia , School of Medicine, 2007)
The study was aimed at determinig knowledge,attitude and practices of emergency contraception among women seeking abortion at kitwe central hospital. The Zambian government endorsed the use of emergency contracepyion in 1997. Since then, the government has mandated the provision and use of EC at all levels of health care delivery. Adoptio of the EC was part of an effort to reduce high incidence of abortion due to unwanted pregnancy.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Emergency contraceptive --Kitwe central hospital --Zambia.; Birth control; Abortion --women --attitudes --Kitwe central hospital --Zambia